FRAME SEMANTICS IN THE DOMAIN OF UNMANNED AERIAL VEHICLES FOR LOGISTICS AND DATA TRANSMISSION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
With the rapid development of Unmanned Aerial Vehicles (UAVs), the demand for precise documentation has become essential. This evolution has introduced a new layer of terminology into Aviation English, as the communication and operational requirements of UAVs differ significantly from those of traditional manned aircraft, particularly in the context of logistics and data transmission. Recognizing this, ICAO and other aviation bodies are working to standardize UAV-related terminology, as inconsistent interpretations can lead to miscommunication. This article provides an overview of frame semantics theory and explores UAV applications in logistics and data transmission. It addresses the significance of frame-based terminology as an analytical tool for understanding the complexities of UAV discourse. Utilizing Sketch Engine, this study analyzes the frequency and collocation patterns of terms within the UAV field, providing valuable insights into the underlying frames that shape technical English in aviation. This analysis highlights multi-word terms and frames, revealing a significantly higher frequency of nouns compared to verbs, indicating a preference for descriptive terminology within the UAV domain. By studying UAV-related terminology, this research offers valuable insights into how technological advancements influence and expand specialized professional languages like aviation English.